Small-incision cataract surgery in patients with Fuch’s heterochromic iridocyclitis - Bhargava, R; Kumar, P; Sharma, SK; Ranjan, S; Kumar, M; Godara, Rohini (Nepalese Journal of Ophthalmology, 2014)
Introduction: Fuch’s heterochromic iridocyclitis (FHI) is often complicated by cataract formation.Objective: To assess the results of small-incision cataract surgery (SICS) in FHI and to study the effect of preoperative factors on postoperative vision.Materials and methods: Sixty-three eyes of 59 patients with Fuchs heterochromic iridocyclitis who had SICS with in-the-bag implantation of intraocular lens (IOL) were evaluated retrospectively; and the primary and secondary outcome measures evaluated were the postoperative vision and complication rate.Results: The mean age was 39.22 ± 4.95 years. The mean pre-operative vision was 0.75 ± 0.24 Log MAR units. The mean final vision was 0.27 ± 0.10 Log MAR units (P = < 0.001). At the final follow-up, 84.1 % of the patients had a final Snellen’s vision of 6/12 or better. The mean follow-up period was 12.06 ± 2.06 months. The causes of corrected distance visual acuity (CDVA) worse than 6/60 were vitreous opacities, posterior keratic precipitates (KPs), glaucoma, persistent uveitis and cystoid macular edema (CME). Preoperative factors like iris atrophy (P = 0.973), heterochromia (P = 0.10) and vessels in angle (P = 0.074) did not have a significant effect on the final vision. On the contrary, vitreous opacities (P = 0.002) and posterior KPs (P = 0.009) had a significant effect on the final visual outcome.Conclusion: SICS with in-the-bag implantation of IOL in patients with Fuch’s heterochromic iridocyclitis resulted in good visual outcomes. SICS in complicated cataracts can be performed in rural settings and eye camps with minimal instrumentation, obviating the need for referral to tertiary care centers. Pre-operative factors like vitreous opacities and posterior KPs have a significant effect on the final vision.DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11705Nepal J Ophthalmol 2014: 6 (12): 153-161